Pengaruh Guncangan Kebijakan Moneter dan Variabel Makro Terhadap Dana Pihak Ketiga (DPK) Bank Syariah di Indonesia - Mohammad Abdul Adim; Raditya Sukmana (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
The purpose of this research is to find out the effect of monetary policy shocks and macro variables towards Islamic banks deposits. The method that used in this researc his quantitative method and also using secondary data which obtained from financial reports and other reports started from 2005 until the end of 2015. Analysis technique used is Johansen Cointegration and Vector Autoregressive (VAR). The result are monetary policy shocks have affect significant on deposits Islamic banks in long run and short run. Furthermore, variables macroeckonomic like GDP and CPI have effect significant on deposits in Islamic banks. interestingly, the money supply in the long run have significant effect on Islaimc banks deposits, but in the short run does not have a significant effect on the deposits of Islamic banks.